Pharmacogenetics of risperidone therapy in autism: association analysis of eight candidate genes with drug efficacy and adverse drug reactions - Correia, C.T. (2011)
Little has been reported on the factors, genetic or other, that underlie the variability in individual response, particularly for autism. In this study we simultaneously explored the effects of multiple candidate genes on clinical improvement and occurrence of adverse drug reactions, in 45 autistic patients who received monotherapy with risperidone up to 1 year. Candidate genes involved in the pharmacokinetics (CYP2D6 and ABCB1) and pharmacodynamics (HTR2A, HTR2C, DRD2, DRD3, HTR6) of the drug, and the brain-derived neurotrophic factor (BDNF) gene, were analysed. Using the generalized estimating equation method these genes were tested for association with drug efficacy, assessed with the Autism Treatment Evaluation Checklist, and with safety and tolerability measures, such as prolactin levels, body mass index (BMI), waist circumference and neurological adverse effects, including extrapyramidal movements. Our results confirm that risperidone therapy was very effective in reducing some autism symptoms and caused few serious adverse effects. After adjusting for confounding factors, the HTR2A c.-1438G>A, DRD3 Ser9Gly, HTR2C c.995G>A and ABCB1 1236C>T polymorphisms were predictors for clinical improvement with risperidone therapy. The HTR2A c.-1438G>A, HTR2C c.68G>C (p.C33S), HTR6 c.7154-2542C>T and BDNF c.196G>A (p.V66M) polymorphisms influenced prolactin elevation. HTR2C c.68G>C and CYP2D6 polymorphisms were associated with risperidone-induced increase in BMI or waist circumference. We thus identified for the first time several genes implicated in risperidone efficacy and safety in autism patients. Although association results require replication, given the small sample size, the study makes a preliminary contribution to the personalized therapy of risperidone in autism.